Analysis of mRNA Expression Patterns in Peripheral Blood Cells of 3 Patients With Cancer After the First Fraction of 2 Gy Irradiation: An Integrated Case Report and Systematic Review. Issue 1 (26th February 2019) - Nie, Yue-Hua; Liu, Xiao-Dan; Huang, Ruixue; Xie, Da-Fei; Yin, Wen-Jun; Guan, Hua; Yu, Zi-Jian; Zhou, Ping-Kun
Background: Radiation therapy induces acute and chronic radiological toxicity, in particular hematological toxicity (HT). This study aimed to explore the mechanistic clue and potential predictors at the messenger RNA (mRNA) level. Materials and Methods: Peripheral blood was collected from 3 patients with cervical cancer (CC), nasopharynx cancer (NC), and tongue cancer (TC) after the first 2 Gy fraction of radiotherapy (RT). High-throughput sequencing was used to assess mRNA profiles. Results: Eleven genes, such as ALAS2(5-aminolevulinate synthase), SLC4A1(solute carrier family 4 member 1), HBG2 (hemoglobin subunit gamma 2), TNFAIP3 (TNF α-induced protein 3), PER1 (period circadian clock 1), CCDC136 (coiled-coil domain containing 136), C9orf84 (chromosome 9 open reading frame 84), IL1B (interleukin 1β), FOSB (FosB protooncogene), NR4A2 (nuclear receptor subfamily 4), PARP15 (polymerase family member 15), had overlapping expression changes in all 3 cancers of which 3 ( ALAS2, FOSB, and HBG2 ) are suggested as potential predictors for the early diagnosis of HT after RT. Conclusions: ALAS2, FOSB, and HBG2 may be useful predictors of HT in patients after RT. Eleven overlapping expression mRNAs among 3 cancers might be potential predictors for early diagnosis of radiation toxicity in patients.